Food Havens: How Social Enterprises Are Shaping Healthy Food Environments for Māori and Pacific Communities in Tāmaki Makaurau - Tonumaipe'a, Daysha (Auckland University of Technology, 2025)
Background & Objective: This study is part of a broader effort to address health inequities, including high levels of obesity, non-communicable diseases, and mortality rates among Māori and Pacific communities in Aotearoa (New Zealand). This study investigates the role of food environments and social enterprise initiatives in creating healthy food spaces for Māori and Pacific Peoples. It examines social enterprise definitions in Tāmaki Makaurau (Auckland), initiatives that promote food sustainability, and their potential impact on Māori and Pacific whānau. Manuscript One has been written to provide context and a literature review that speaks to food environments and how the body of literature can be viewed from a Māori and Pacific lens. Research Design: Underpinned by Māori and Pacific paradigms, this study uses the Moana Māori methodology, developed and proposed in Manuscript Two. A total of 47 participants took part in this study, contributing through in-depth interviews, talanoa (inclusive dialogue) and wānanga (discussion and deliberation). Eleven participants led social enterprises focused on healthy food environments, whilst 36 end-users shared their perspectives. Data was analysed thematically. Findings & Discussion: This study highlights the impact of social, cultural, and economic factors on Māori and Pacific communities. Key challenges include the prevalence of fast food, economic constraints, and time poverty. Positive strategies include urban home gardening, social enterprise engagement, and community support. Social enterprises, schools, marae, and churches play critical roles in promoting food sovereignty and healthier diets, emphasising the need for culturally aligned, community-led initiatives to address health inequities. This study explores how these social enterprises address food insecurity and promote food sovereignty, focusing on community-led initiatives, the preservation of traditional food practices, and advocacy for policy change. It introduces the concept of ‘social food environments’ that integrates social, cultural, and spiritual dimensions, and proposes a Food Havens Framework to align food systems with Indigenous values. This study calls for continued support for such initiatives to improve public health. The findings of this study are also presented in Manuscript Three, which explores social enterprises as an upstream healthcare model that may improve food environments for Māori and Pacific peoples. Conclusion: This study extends our understanding of social enterprises and healthy food environments for Māori and Pacific communities. It offers both practical and theoretical insights into addressing health inequities, with implications for public health policy and future research on social issues impacting these communities.